1991
DOI: 10.1113/jphysiol.1991.sp018675
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of prediction in human smooth pursuit eye movements.

Abstract: 1. Experiments have been conducted on human subjects to determine the role of prediction in smooth eye movement control. Subjects were required to actively pursue a small target or stare passively at a larger display as it moved in the horizontal plane. 2. Target motion was basically periodic, but, after a random number of cycles an unexpected change was made in the amplitude, direction or frequency of target motion. Initially, the periodic stimulus took the form of a square waveform. In subsequent experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
181
4
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(202 citation statements)
references
References 31 publications
16
181
4
1
Order By: Relevance
“…Previous work on sequence learning has suggested that the anticipatory advantage of predictive eye movements is based upon the short-term storage of a pre-motor instruction set required for that eye movement (pursuit: Barnes & Asselman, 1991;Barnes & Donelan, 1999. saccades: Walker & McSorley, 2006Burke & Barnes, 2008a;Collins & Wallman, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work on sequence learning has suggested that the anticipatory advantage of predictive eye movements is based upon the short-term storage of a pre-motor instruction set required for that eye movement (pursuit: Barnes & Asselman, 1991;Barnes & Donelan, 1999. saccades: Walker & McSorley, 2006Burke & Barnes, 2008a;Collins & Wallman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Saccadic latency decreases with sequence repetition and the eye movements can even occur in advance of the onset of a new fixation stimulus (Gaymard, Pierrot-Deseilligny & Rivaud, 1990;Petit, Clark & Ingeholm, 1996;Schmid, Rees, Frith & Barnes, 2001;Barnes & Schmid, 2002;Simo, Krisky & Sweeney, 2005;Burke & Barnes 2007). In making these eye movements, observers can in effect anticipate future target locations based upon the spatial and temporal information pertaining to that specific sequence retained by memory mechanisms (Carpenter, 1988;Barnes & Asselman 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive estimations are internally generated and utilized in skilled behaviour to minimise error and decrease processing delays in the sensorimotor system. Both saccadic and pursuit eye movements exhibit this predictive behaviour during repeated stimulus presentations involving the use of short-term memory storage (Barnes & Asselman, 1991) and much is now known about the mechanisms that guide these behaviours (for pursuit, see Barnes & Asselman, 1991;Missal & Heinen, 2004;Schmid, Rees, Frith, & Barnes, 2001; for saccades, see Lu, Matsuzawa, & Hikosaka, 2002). In addition, there is now substantial evidence of some commonalities in the neural networks between these two eye movement types (Krauzlis, 2005;Nyffeler, Rivaud-Pechoux, Wattiez, & Gaymard, 2008;Orban de Xivry & Lefèvre, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are inherent differences between the two eye movement types, in that pursuit eye movements normally rely on error correction obtained from stimulus feedback (Barnes & Asselman, 1991), whilst saccades are considered ballistic movements and can be initiated in the absence of a visual stimulus (Leigh & Zee, 1991). Furthermore, prediction in pursuit is observed after previously sampling the stimulus or cueing (Barnes & Asselman, 1991;Barnes & Donelan, 1999;Becker & Fuchs, 1985); whilst prediction in saccades can occur without this previous sampling, but wrong predictions are associated with certain costs (i.e., accuracy and timing). Thus, investigations into the learning mechanisms of these two systems will provide further insight into how the central nervous system combines different modes of motor control to achieve a common goal.…”
Section: Introductionmentioning
confidence: 99%